Revenue for EMU: A Contribution to the Debate on Fiscal Union - Anna Iara (Center for Economic Studies and ifo Institute (CESifo), 2016)
In the wake of the euro area crisis, the debate on instruments to deepen economic integration among its members has intensified, among others putting forward a fiscal stabilization capacity for EMU members. Contributions made so far to further this idea have mostly concentrated on the expenditure side and possible stabilisation properties. This analysis reviews the most important proposals and discusses design choices and institutional conditions to develop the revenue side of such a fiscal instrument.
Keywords: H29; H77; H87; 330; European Union; EMU; fiscal federalism; fiscal integration; EU budget